Robust Stability Control for Electric Vehicles Connected to DC Distribution Systems - Teng, Wei; Wang, Yuejiao; Sun, Shumin; Cheng, Yan; Yu, Peng; Wang, Shibo (Frontiers in Energy Research, 2021)
DC power distribution systems will play an important role in the future urban power distribution system, while the charging and discharging requirements of electric vehicles have a great impact on the voltage stability of the DC power distribution systems. A robust control method based on H∞ loop shaping method is proposed to suppress the effect of uncertain integration on voltage stability of DC distribution system. The results of frequency domain analysis and time domain simulation show that the proposed robust controller can effectively suppress the DC bus voltage oscillation caused by the uncertain integration of electric vehicle, and the robustness is strong.